Identification of the Mycobacterium ulcerans protein MUL_3720 as a promising target for the development of a diagnostic test for Buruli ulcer. - Anita Dreyer; Katharina Röltgen; Jean Pierre Dangy; Marie Thérèse Ruf; Nicole Scherr; Miriam Bolz; Nicholas Jay Tobias; Charles Moes; Andrea Vettiger; Timothy Paul Stinear; Gerd Pluschke (Public Library of Science (PLoS), 2015)
Buruli ulcer (BU) caused by Mycobacterium ulcerans is a devastating skin disease, occurring mainly in remote West African communities with poor access to health care. Early case detection and subsequent antibiotic treatment are essential to counteract the progression of the characteristic chronic ulcerative lesions. Since the accuracy of clinical BU diagnosis is limited, laboratory reconfirmation is crucial. However, currently available diagnostic techniques with sufficient sensitivity and specificity require infrastructure and resources only accessible at a few reference centres in the African endemic countries. Hence, the development of a simple, rapid, sensitive and specific point-of-care diagnostic tool is one of the major research priorities for BU. In this study, we have identified a previously unknown M. ulcerans protein, MUL_3720, as a promising target for antigen capture-based detection assays. We show that MUL_3720 is highly expressed by M. ulcerans and has no orthologs in other prevalent pathogenic mycobacteria. We generated a panel of anti-MUL_3720 antibodies and used them to confirm a cell wall location for MUL_3720. These antibodies could also specifically detect M. ulcerans in infected human tissue samples as well as in lysates of infected mouse footpads. A bacterial 2-hybrid screen suggested a potential role for MUL_3720 in cell wall biosynthesis pathways. Finally, we demonstrate that a combination of MUL_3720 specific antibody reagents in a sandwich-ELISA format has sufficient sensitivity to make them suitable for the development of antigen capture-based diagnostic tests for BU.